ANALISIS FINANSIAL EKOWISATA HUTAN MANGROVE DI SEBUBUS KECAMATAN PALOH (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
Ecotourism is one of the tourism support conservation effort. This tourism is also give a good appreciation to its environment, culture, history and local community participation. The ecotourism development in Sebubus mangrove area is initiated as an effort for tourism development that can support the conservation of mangrove forest that could potentially raise incomes and welfare support for local people.Location of this research at Sebubus Paloh. Data used in this research is primary data. Data analysis was using financial analysis with indicator : Net Present Value, Internal Rate of Return, Net Benefit Cost Ratio, Payback Period, Sensitivities analysis.The result of this study show that : ecotourism mangrove forest is feasible by considering NPV = Rp. 4.188.742, IRR = 21,68% dan Net B/C = 3,5, payback period is 11 months. Sensitivity analysis with 10% benefits reduction scenarios is feasible. Keywords :ecotourism, financial analysis, mangrove forest, Paloh